"L" is for lawless - Grafton, Sue frey50 (Henry Holt New York, NY, 1995)
Kinsey's skills are about to be sorley tested. She is about to meet her duplicitous match in a couple of world-class prevaricators who quite literally take her for the ride of her life.
Keywords: Millhone, Kinsey (Fictious character); Women detectives--Fiction; California--Fiction; Mystery fiction; Mystery fiction